Cold-atom optical filtering enhanced by optical pumping - Guan, Xiaolei; Zhuang, Wei; Shi, Tiantian; Miao, Jianxiang; Zhang, Jia; Chen, Jingbiao; Luo, Bin (Frontiers in Physics, 2022)
Atomic optical filters such as Faraday anomalous dispersion optical filters (FADOFs) or similar technologies can achieve very narrow optical bandwidth close to the scale of atomic linewidth, which can be greatly reduced in cold atoms. However, limited by the number of cold atoms and the size of the cold atomic cloud, the number of atoms interacting with the laser is reduced, and the transmission remains as low as 2%. In this work, we introduce the optical pumping into the cold atomic optical filter to solve this problem. Circular polarized optical pumping can produce polarization of the atomic ensemble and induce dichromatic as well as the Faraday rotation. We demonstrate a cold-atom optical filter which operates on the 87Rb 52S1/2 (F=2) to 52P3/2 (F'=2) transition at 780 nm. The filter achieves an ultranarrow bandwidth of 6.6(4) MHz, and its peak transmission is 15.6%, which is nearly 14 times higher than that of the cold-atom optical filter realized by Faraday magneto-optic effect. This scheme can be extended to almost all kinds of atomic optical filters and may find applications in self-stabilizing laser and active optical clock.